An Application for Calculating the Qibla Direction Angle Relative to Buildings - Yasri, Yasri (Journal of Artificial Intelligence and Software Engineering, 2025)
The challenges associated with accurate Qibla direction determination, particularly in urban environments are solved by introducing an innovative web-based application designed to overcome these limitations. To the best of our knowledge, no application has previously employed this method to determine the Qibla direction. While existing Qibla pointing applications often rely on outdated data or are prone to magnetic anomalies, this application calculates the deviation of the Qibla angle relative to the orientation of the building, thus providing a more reliable and user-friendly solution. By combining precise coordinate data and visual alignment tools, the app allows users to align a virtual line with the position of the building and calculate the exact angular difference between this alignment and the true Qibla direction. This approach reduces errors arising from incompatible coordinate data and environmental factors, and offers a context-appropriate tool to ensure accurate prayer alignment. The app aims to provide a reliable means for Muslims around the world to fulfill their religious obligations with greater precision, contributing to the advancement of direction-finding technology.